Variation in Anti-icing Power of Superhydrophobic Electrothermal Film under Different Temperatures and Wind Speeds - Shijie Xue; Yihua Liu; Yu Wang; Bing Xiao; Xiaoxin Shi; Jingchun Yao; Xianglian Lv; Weizheng Yuan; Yang He (International Journal of Aerospace Engineering)
Anti-icing with low-energy consumption has important research value for unmanned aerial vehicles. In this study, a superhydrophobic electrothermal film for anti-icing applications was designed and prepared, and power consumption experiments were conducted at different temperatures and wind speeds in an icing wind tunnel. The anti-icing power consumption of the superhydrophobic electrothermal film was lower than that of a traditional electrothermal film. As the temperature decreased or the wind speed increased, the anti-icing power consumption of the two types of electrothermal films increased. A heat flux model was used to analyse the experimental results. It can be concluded that the water collection rate per unit area W and wetting coefficient ξw are the main factors affecting the power consumption of the superhydrophobic electrothermal film. When the temperature decreased and the wind speed increased, the contact time and contact area between the droplet and the surface affected W and ξw. Thus, this study is of considerable significance for the design of superhydrophobic electrothermal films for novel anti-icing applications in the future.